Effect of gas metal arc welding parameters on the behaviour of heat affected zone of 316l ss and a572 gr. 50 steel - Deo, Manish (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Effect of gas metal arc welding; parameters on the behaviour of; heat affected zone of; 316l ss and a572 gr. 50 steel